An Optimization Method for Cutting Stock Problem with Complex Application Requirements in Cloud Manufacturing. Issue 4 (December 2018) - Wu, Dianjian; Yan, Chunping
Abstract: Aiming at that the existing optimization algorithms for cutting stock problem are unable to satisfy cutting stock problem with complex application requirements in continuous cutting stock process, an optimization method for cutting stock problem with complex application requirements is proposed from the perspective of cloud manufacturing. Meanwhile, a cloud service platform of cutting stock system is constructed to achieve this method in cloud manufacturing. Three key technologies for cutting stock cloud service, including classification management of cloud service, search matching of cloud service, dynamic scheduling of cloud service, are studied in this service platform. The feasibility of the proposed method for cutting stock problem with complex application requirements is verified by building the basic framework of the prototype system.